Abatacept in IgG4-related disease: a prospective, open-label, single-arm, single-centre, proof-of-concept study. (February 2022) - Matza, Mark A; Perugino, Cory A; Harvey, Liam; Fernandes, Ana D; Wallace, Zachary S; Liu, Hang; Allard-Chamard, Hugues; Pillai, Shiv; Stone, John H
Summary: Background: There is strong rationale behind interfering with T-cell co-stimulation in the treatment of IgG4-related disease, but the literature is limited to a single case report. We therefore aimed to investigate the potential efficacy and safety of abatacept, which blocks co-stimulatory signal delivery to naive T cells, in the treatment of IgG4-related disease. Methods: This prospective, open-label, single-arm, single-centre, proof-of-concept study was done in Massachusetts General Hospital, Boston, MA, USA. Eligible participants were at least 18-years-old, fulfilled the 2019 American College of Rheumatology and European League Against Rheumatism classification criteria for IgG4-related disease, and had active disease, as defined by an IgG4-related disease responder index of at least 2 at screening. Participants received 125 mg of subcutaneous abatacept weekly for 24 weeks. Concurrent glucocorticoid treatment was permitted but had to be discontinued by week 4. Peripheral blood mononuclear cells were collected at baseline, 4 weeks, and 12 weeks, and B-cell and T-cell subsets were quantified by use of a 25-parameter flow cytometry panel. The primary endpoint was complete remission of IgG4-related disease at 24 weeks, defined by an IgG4-related disease responder index of 0, a prednisone dose of 0 mg/day beyond week 4, and no recurrence of disease activity since the baseline visit. All outcomes were analysed via intention-to-treat. This trial was registered at ClinicalTrials.gov, NCT03669861, and is complete. Findings: Between Dec 5, 2018, and Aug 22, 2019, ten patients were screened for eligibility, all of whom were enrolled. Seven (70%) of ten participants were male and nine (90%) were White. Baseline organ involvement was diverse, with a median of five organs (IQR 3–5) affected at the time of enrolment. Three participants received concomitant prednisone at baseline. At 24 weeks, three (30%) participants had complete remission. Higher baseline proportions of unswitched memory B cells were associated with responsiveness to abatacept. Reductions from baseline in serum IgE concentrations, circulating plasmablasts, and activated type 2 T follicular helper cells were associated with response to treatment. One adverse event (grade 2 thrombocytopenia) was attributed to abatacept and there were no treatment-related deaths. Interpretation: Abatacept was associated with variable treatment responses in patients with IgG4-related disease. Our findings could inform future studies of immunological therapies for the treatment of IgG4-related disease. Funding: Bristol Myers Squibb and the National Institutes of Health.